An Open-Label, Dose-Escalation Phase I Study of Anti-TYRP1 Monoclonal Antibody IMC-20D7S for Patients with Relapsed or Refractory Melanoma - Khalil, Danny N; Postow, Michael A; Ibrahim, Nageatte; Ludwig, Dale L; Cosaert, Jan; Kambhampati, Siva Rama Prasad; Tang, Shande; Grebennik, Dmitri; Kauh, John Sae Wook; Lenz, Heinz-Josef; Flaherty, Keith T; Hodi, F Stephen; et al. (Clinical cancer research, 2016)
PURPOSE: Tyrosinase-related protein-1 (TYRP1) is a transmembrane glycoprotein that is specifically expressed in melanocytes and melanoma cells. Preclinical data suggest that mAbs targeting TYRP1 confer antimelanoma activity. IMC-20D7S is a recombinant human IgG1 mAb targeting TYRP1. Here, we report the first-in-human phase I/Ib trial of IMC-20D7S. EXPERIMENTAL DESIGN: The primary objective of this study was to establish the safety profile and the MTD of IMC-20D7S. Patients with advanced melanoma who progressed after or during at least one line of treatment or for whom standard therapy was not indicated enrolled in this standard 3 + 3 dose-escalation, open-label study. IMC-20D7S was administered intravenously every 2 or 3 weeks. RESULTS: Twenty-seven patients were enrolled. The most common adverse events were fatigue and constipation experienced by nine (33%) and eight (30%) patients, respectively. There were no serious adverse events related to treatment, no discontinuations of treatment due to adverse events, and no treatment-related deaths. Given the absence of dose-limiting toxicities, an MTD was not defined, but a provisional MTD was established at the 20 mg/kg every 2-week dose based on serum concentration and safety data. One patient experienced a complete response. A disease control rate, defined as stable disease or better, of 41% was observed. CONCLUSION: IMC-20D7S is well tolerated among patients with advanced melanoma with evidence of antitumor activity. Further investigation of this agent as monotherapy in selected patients or as part of combination regimens is warranted. Clin Cancer Res; 22(21); 5204-10. ©2016 AACR.
Keywords: rozvrh dávkování léků; vztah mezi dávkou a účinkem léčiva; Female; imunoglobulin G; ženské pohlaví; Membrane Glycoproteins; Antibodies, Monoclonal; lidé; rekombinantní proteiny; Recombinant Proteins; Antineoplastic Agents; protinádorové látky; Drug Administration Schedule; Aged, 80 and over; Immunoglobulin G; Dose-Response Relationship, Drug; Male; melanom; Aged; Oxidoreductases; oxidoreduktasy; monoklonální protilátky; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; membránové glykoproteiny; Middle Aged; Melanoma; Humans